2021
DOI: 10.3389/fmolb.2021.668402
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Prognostic Value of MCM Family Genes in Osteosarcoma

Abstract: We performed a detailed cancer VS normal analysis to explore the expression and prognostic value of minichromosome maintenance (MCM) proteinsin human sarcoma. The mRNA expression levels of the MCM family genes in sarcoma were analyzed using data from ONCOMINE, GEPIA and CCLE databases. KEGG database was used to analyze the function of MCM2–7 complex in DNA replication and cell cycle. QRT-PCR and western blot were used to confirm the differential expression of key MCMs in osteosarcoma cell lines. Cell Counting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…Jian Zhou et al reported that MCMs were generally upregulated in various of tumors. Consistent with our research, most of MCM members were highly expressed in tumor tissues, except for MCM8 and MCM9 in sarcoma (32). The proliferation of osteosarcoma cells could be restrained by the inhibition of MCM2.…”
Section: Discussionsupporting
confidence: 91%
“…Jian Zhou et al reported that MCMs were generally upregulated in various of tumors. Consistent with our research, most of MCM members were highly expressed in tumor tissues, except for MCM8 and MCM9 in sarcoma (32). The proliferation of osteosarcoma cells could be restrained by the inhibition of MCM2.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the hypermethylation state was significantly correlated with MCM3overexpression. Previous studies also reported that MCM3 hypomethylation could increase its expression in hepatocellular carcinoma ( Hua et al, 2020 ) and osteosarcoma ( Zhou et al, 2021 ), and was negatively associated with prognosis. We also identified that “double-strand break repair via break-induced replication” might be the most affected biological processes in GSEA of MCM3 correlated and differential genes between the high and low MCM3 expression groups ( Figure 3B ).…”
Section: Discussionmentioning
confidence: 87%
“…Many studies have clarified the molecular mechanism and prognostic markers of various subtypes of sarcoma from the perspective of gene expression. 10–12 , 14 , 26 , 27 However, the prognostic value of the differential expressed genes in the integrated subtypes of sarcoma remains to be reported. In this study, we obtained three GSE series profiles from the GEO database, and differentially expressed genes were selected.…”
Section: Discussionmentioning
confidence: 99%
“… 13 Similarly, minichromosome maintenance family proteins were found to widely participate in the tumor progress and prognosis in patients with osteosarcoma. 14 However, the role of common differential expression genes (CDEGs) among diverse subtypes of SARC has not been reported. In the current study, we obtained several CDEGs from three GEO series (GSE) profiles and identified several genes that interacted the most.…”
Section: Introductionmentioning
confidence: 99%